First day bilirubin as a predictor of development of significant jaundice in term healthy neonates: a tertiary care hospital based study - Hussain, Malik Shakir; Gattoo, Imran Ahmad; Najar, Bilal Ahmad; Maqbool, Muddasir (International Journal of Contemporary Pediatrics, 2017)
Background: Neonatal jaundice is common and usually benign self-limited condition, but if severe can cause severe neurological damage.1 This prospective study was undertaken to determine the critical serum bilirubin level to predict the significant hyperbilirubinemia in healthy term new-borns based on the serum bilirubin measurement made within 24 hours of postnatal life. Present study was done to study the first day bilirubin as a predictor of development of significant jaundice in healthy term neonates. Methods: The present study was conducted in the post graduate department of paediatrics Government Medical College Srinagar, tertiary care referral hospital. Total of 152 healthy term new-borns were included in the study. Micro capillary sample was taken on heel prick and centrifuge. Bilirubin estimation was done spectophotometrically using twin beam method (575-455) wave length bilinmicrometer. The infants were followed up clinically every 12 hours after initial bilirubin estimation till discharge the babies were recalled after discharge at 5 days of age. This study is a Prospective observational study. Results: Initial bilirubin estimation was done on first postnatal day, and the range of initial bilirubin estimation was between 2.9-8 mg/dl. Clinically detectable jaundice was present in 110 (72.36%) patients. Out of 152 new-borns, 101 (66.44%) with serum bilirubin <6 mg/dl only 1 developed significant hyperbilirubinemia, were as 51 (33.52%) new-borns who had serum bilirubin >6 mg/dl 13 (25.46%) developed significant hyperbilirubinemia. Conclusions: The present study found that a total serum bilirubin level of ≤6 mg/dl can be used to predict decreased risk for subsequent hyperbilirubinemia (TSB >17 mg/dl) with a sensitivity of 92.8% and negative predictive value of 99%. Such infants could thus be discharged early without need to follow up for hyperbilirubinemia later.